2016
DOI: 10.1042/cs20150591
|View full text |Cite
|
Sign up to set email alerts
|

Potent irreversible P2Y12 inhibition does not reduce LPS-induced coagulation activation in a randomized, double-blind, placebo-controlled trial

Abstract: Platelets play an important role in the activation of coagulation. P2Y12 receptor inhibition may be beneficial in inflammatory states. Prasugrel, a potent irreversible inhibitor of P2Y12 receptor-induced platelet activation may reduce activation of coagulation in a human LPS (lipopolysaccharide) model. A double-blind, randomized, crossover trial with a minimum washout period of 6 weeks was performed. Sixteen subjects were randomly assigned to a treatment group that received prasugrel or placebo 2 h before infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
3
14
0
1
Order By: Relevance
“…Sepsis is an acute reaction to a systemic pathogenic microorganism insult, resulting in uncontrolled activation of inflammation, with concomitant activation of the coagulation system, resulting in pathologic immunothrombosis . Previous reports have demonstrated that VWF , CF‐DNA and nucleosome levels are elevated in patients with severe sepsis and in human LPS trials . We further demonstrated that, in both septic patients and a murine model of endotoxemia, plasma levels of WPB‐released proteins and CF‐DNA were elevated; however, no correlation was observed (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Sepsis is an acute reaction to a systemic pathogenic microorganism insult, resulting in uncontrolled activation of inflammation, with concomitant activation of the coagulation system, resulting in pathologic immunothrombosis . Previous reports have demonstrated that VWF , CF‐DNA and nucleosome levels are elevated in patients with severe sepsis and in human LPS trials . We further demonstrated that, in both septic patients and a murine model of endotoxemia, plasma levels of WPB‐released proteins and CF‐DNA were elevated; however, no correlation was observed (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Platelet-monocyte aggregates are known to amplify monocyte release of proinflammatory cytokines that are responsible for the excessive immune response in sepsis, and their prevention could therefore be beneficial [50,51]. Consistent with the absent response of platelet-neutrophil aggregation upon P2Y 12 inhibition in the study by Thomas et al [48], another human experimental endotoxemia study by Schoergenhofer et al [17] found no influence of prasugrel on circulating levels of histone-DNA complexes. The latter serve as surrogates of extracellular traps derived from neutrophils (NETs), which can be formed following platelet toll-like receptor 4-mediated platelet-neutrophil aggregation [52].…”
Section: Discussionmentioning
confidence: 62%
“…However, both mechanisms are unlikely since clopidogrel and ticagrelor showed indistinguishable effects on circulating miRNAs; despite ticagrelor being an allosteric antagonist that does not require enzymatic activation and is present continuously in the plasma at therapeutic concentrations during treatment [45]. Instead, there is evidence that P2Y 12 inhibitors insufficiently reduce platelet reactivity during sepsis [15][16][17]. Patients on clopidogrel upon sepsis onset showed high on-treatment platelet reactivity in a prospective observational study, as determined by the VerifyNow point-of-care P2Y 12 assay [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16, 21 In fact, rabbits are notably less resistant to LPS than mice, although these non-rodents are still far from the exquisite sensitivity of humans to endotoxin. Thus, in current human studies, 2 ng kg −1 of LPS were used to induce endotoxemia; 22, 23, 24 however, in rabbits, a range of 1–10 μg kg −1 is applied in i.v. applications.…”
Section: Discussionmentioning
confidence: 99%